Efecto de cuatro dosis de calcio en el rendimiento y calidad de turiones de espárrago blanco (asparagus officinalis l.) var. uc-157 f1, en VIRÚ - LA LIBERTAD - López Aguilar, Jayné Juliana (2013)
This paper "Effect of four doses of calcium on yield and quality of white asparagus spears (Asparagus officinalis L.) var. UC-157 F1, in Virú - La Libertad ", whose main objective was to assess which of the four doses of calcium was obtained the highest performance and the best commercial quality of white asparagus spears (Asparagus officinalis L.) var. UC-157 F1, in Virú - La Libertad. The work took place during the months of August 2012 to December 2012, in the San José located in the district Chao, Virú province, in the department of La Libertad. Statistical design was used in randomized complete block with 5 treatments and 3 repetitions. Factors in study were asparagus variety F1 and UC-157 doses of calcium oxide: 0, 40, 60, 80, 100. The results obtained indicate that: With the T4, which is the calcium doses of 100 units of CaO, higher yields and better quality commercial shoots of white asparagus (Asparagus officinalis L.) var was reached. UC-157 F1, in Virú - La Libertad. With the T4, which is the calcium doses of 100 units of CaO, lower weight (kg) was obtained by treatment of spears of white asparagus (Asparagus officinalis L.) var. UC-157 F1, in Virú - La Libertad features: jumbo crowns, crowns with mild cracked, discard mushy crowns, crowns with strong discard cracked, discard jumbo spears.